Prospective study of protein intake and mortality among US adults with chronic obstructive pulmonary disease - Lu, HuiLun; Zhang, Qi; Long, Jiao (Frontiers in Nutrition, 2024)
Background: Protein is crucial for the rehabilitation of patients with chronic obstructive pulmonary disease (COPD), and appropriate daily protein intake is essential for COPD patients. However, the specific role of protein intake in COPD and its impact on mortality remain uncertain. This study aims to ascertain the relationship between protein intake and mortality in COPD patients. Methods: This investigation included 522 adult COPD patients from the National Health and Nutrition Examination Survey (NHANES) between 2013 and 2018, with a focus on evaluating protein intake. Multivariate Cox proportional hazard models were constructed to analyze the correlation between protein intake and the prognosis of COPD patients. Additionally, the restricted cubic spline (RCS) was employed to investigate the potential non-linear association between protein intake and mortality. Results: A total of 522 patients with COPD were categorized into 4 groups based on the quartiles of protein intake: Q1 (< 25th percentile, 11.7-48.5 gm), Q2 (25-50th percentile, 48.5-67.7 gm), Q3 (50-75th percentile, 67.7-94.3 gm), and Q4 (≥ 75th percentile, 94.3-266.6 gm). Cox regression analysis revealed a significant trend in the p value of the Q3 group compared to the Q1 group when adjusting for other variables. The RCS-fitted Cox regression model indicated no non-linear relationship between protein intake levels and COPD mortality. Conclusion: There is no evidence of a non-linear relationship between protein intake and all-cause mortality in COPD patients. Further investigation is warranted to comprehend the intricate relationship between protein intake and COPD outcomes.